2011
DOI: 10.1299/jmmp.5.849
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Friction Welding Condition and Weld Faying Surface Properties on Tensile Strength of Friction Welded Joint between Pure Titanium and Pure Copper

Abstract: This paper describes the effect of the friction welding condition and the weld faying surface properties on the tensile strength of the friction welded joint between pure titanium (Ti) and pure copper (OFC). The joint strength of the joint, which was made with the weld faying surface of the Ti side specimen finished with a surface grinding machine, was investigated. The joint did not have 100% efficiency and OFC side fracture regardless of the friction welding conditions. When the joint was made with a frictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…5. A similar mechanically mixed layer was also observed even in several friction welded joints for dissimilar materials combination as reported by many researchers (Ruge, et al, 1986;Yilmaz, et al, 1996;Fuwano, et al, 2000;Straffelini, et al, 2004;Meshram, et al, 2007;Arivazhagan, et al, 2008;Kimura, et al, 2011) in addition to CP-Al/OFC joint (Aritoshi, et al, 1991;Kimura, et al, 2015). Figure 8 shows the cross-sectional appearances of the weld interfaces of joints at various friction times.…”
Section: Transitional Changes Of Weld Interfacesupporting
confidence: 82%
See 2 more Smart Citations
“…5. A similar mechanically mixed layer was also observed even in several friction welded joints for dissimilar materials combination as reported by many researchers (Ruge, et al, 1986;Yilmaz, et al, 1996;Fuwano, et al, 2000;Straffelini, et al, 2004;Meshram, et al, 2007;Arivazhagan, et al, 2008;Kimura, et al, 2011) in addition to CP-Al/OFC joint (Aritoshi, et al, 1991;Kimura, et al, 2015). Figure 8 shows the cross-sectional appearances of the weld interfaces of joints at various friction times.…”
Section: Transitional Changes Of Weld Interfacesupporting
confidence: 82%
“…7b). Hence, it is desirable to be set of an opportune friction time which generate less mechanically mixed layers of the joint because that layer will be affected to the joint strength (Aritoshi, et al, 1991;Kimura, et al, 2011Kimura, et al, , 2015 in addition to the IMC interlayer as reported by some researchers (Nakanishi, et al, 1976;Lee, et al, 2005;Chen, et al, 2006;Saeid, et al, 2010;Wei, et al, 2016). However, all joints fractured from the weld interface as shown in Fig.…”
Section: Transitional Changes Of Weld Interfacementioning
confidence: 93%
See 1 more Smart Citation
“…The materials were machined to 12 mm diameters for the weld faying (contacting) surface (referred to as faying surface). All faying surfaces of specimens were polished with a surface grinding machine before joining in order to eliminate the effect of surface roughness on the mechanical properties of dissimilar material joints (Fuji, et al, 1994;Kimura, et al, 2005cKimura, et al, , 2011b.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the authors also clarified the joining mechanism and the joint mechanical properties of friction welded joint for some dissimilar material joints as following combinations: Al-system materials and low carbon steel (LCS) (Kimura, et al, 2009a(Kimura, et al, , 2009b(Kimura, et al, , 2013, Cu-system materials and LCS (Kimura, et al, 2009c(Kimura, et al, , 2009d, pure Ti and LCS (Kimura, et al, 2014), and pure Cu and pure Ti (Kimura, et al, 2011a(Kimura, et al, , 2011b. If combinations of dissimilar materials such as Al-system materials and Cu-system materials can be joined using the same welding method as that shown in previous reports (Kimura, et al, 2002a(Kimura, et al, , 2002b(Kimura, et al, , 2002c(Kimura, et al, , 2003a(Kimura, et al, , 2003b2005a;2005b, 2009a, 2009b, 2009c, 2009d, 2011a, 2011b, 2013, 2014, the joining mechanism will be clarified. In particular, to clarify the relationship between joining phenomena and tensile strength of that combination joint is strongly important, because that will be estimated for expansion in the use of the electricity industry field.…”
Section: Introductionmentioning
confidence: 99%